2020
DOI: 10.3390/cancers12010247
|View full text |Cite
|
Sign up to set email alerts
|

Sterol O-Acyl Transferase 1 as a Prognostic Marker of Adrenocortical Carcinoma

Abstract: Adrenocortical carcinoma (ACC) is a rare endocrine malignancy with an unfavorable prognosis. Despite the poor prognosis in the majority of patients, no improvements in treatment strategies have been achieved. Therefore, the discovery of new prognostic biomarkers is of enormous interest. Sterol-O-acyl transferase 1 (SOAT1) is involved in cholesterol esterification and lipid droplet formation. Recently, it was demonstrated that SOAT1 inhibition leads to impaired steroidogenesis and cell viability in ACC. To date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
(25 reference statements)
1
21
0
2
Order By: Relevance
“…Malignancies develop protector mechanisms for self-survival. Generally, defects are harbored in evolutionarily conserved pathways, such as the Wnt/β-catenin pathway [ 39 ]. However, nine acquired biological capabilities, known as cancer hallmarks, are involved in a multistep tumorigenesis process [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignancies develop protector mechanisms for self-survival. Generally, defects are harbored in evolutionarily conserved pathways, such as the Wnt/β-catenin pathway [ 39 ]. However, nine acquired biological capabilities, known as cancer hallmarks, are involved in a multistep tumorigenesis process [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of Wnt/β-catenin signaling has been established in different malignancies [ 37 , 84 , 85 ]. ZNRF3 acts as a tumor suppressor of the Wnt/β-catenin pathway [ 39 , 68 , 69 , 86 , 87 , 88 ]. Tissier et al have already demonstrated the role of Wnt/β-catenin in adrenal tumorigenesis [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, large tumour size and cortisol-secreting tumour were additional factors for ACC-specific death [ 49 ]. Moreover, there are many predictive features proposed for the prognosis of patients with ACC such as mitotic grading [ 52 ], Ki-67 index [ 75 ], mi-RNAs expression [ 76 ], expression of PDL-1 [ 77 ], SF-1 [ 78 ] and sterol-O-acyl transferase 1 (SOAT1) [ 79 ]. Preliminary data also shows that for localised ACC, molecular makers (expression, methylation, and chromosome alterations) could predict cancer recurrence [ 9 ].…”
Section: Conventional Adrenocortical Carcinomamentioning
confidence: 99%
“…Studies of molecular prognostic markers of ACC are limited. Lacombe et al reported sterol-O-acyl transferase 1 as a prognostic marker (41). A simple prognostic marker based on the differential expression of two genes (BUB1B-PINK1) was developed by de Reyniès (42).…”
Section: Discussionmentioning
confidence: 99%